(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Building trust in the workplace is one of the most critical factors in sustaining organizational success, and Human Resource Management (HRM) plays a central role in shaping this trust. Employees are more likely to commit to their roles and align with company goals when they feel secure, respected, and valued. HRM acts as both a mediator and an architect of trust through transparent communication, fair policies, consistent leadership practices, and a strong emphasis on employee development. In addition, HR ensures that wellbeing and psychological safety are woven into the culture of work, creating an environment where individuals can thrive. The process of trust-building goes beyond enforcing rules; it is about fostering authentic relationships and creating systems where people feel heard and supported. Trust is eroded when employees perceive bias, secrecy, or inconsistency in organizational practices. HR counters this risk by designing frameworks that encourage openness, accountability, and equitable opportunities. By empowering employees with development pathways, recognizing their contributions, and protecting their wellbeing, HR cultivates not only trust but also long-term loyalty. As organizations adapt to rapid technological and social changes, the role of HRM in building trust becomes even more important. Workforces today demand transparency, fairness, and growth opportunities, and HR must evolve to meet these expectations. Trust is not a one-time achievement but an ongoing commitment, and HR is the custodian responsible for sustaining it across all levels of the workplace.